A comparative study of financial performance of Islamic banks and conventional banks in indonesia - Norhayati, Abdullah (2011)
The paper compared and examinedfinancial performance of Islamic banks against conventional banks beforeand afterthe enactment of Indonesia’s Islamic Banking Act No. 21/2008. The lawaimsto strengthen the regulatory environment for further growth of Indonesia’s market Islamic finance. The datawas based onselected financial statements of Islamic commercial banks in Indonesia from year2000to 2007. Financial performance measures were expressed in terms of various financial ratios in which were categorized intoprofitability, liquidity, risk and solvency and efficiency. To testthe hypotheses, Mann-Whitney was employed to compare financial performance of Islamic banks and conventionalbanks.In general, the study found no major difference in financial performance between Islamic banks and conventional banks, except in terms of its liquidity. This indicated that Islamic banks are generally more liquid as compared to conventional ones.